Identifikasi Penyebaran Bencana Longsor Di Kecamatan Sentani Kota, Kabupaten Jayapura - Predy Taplo; Monita Y. Beatrick Wambrauw; Tommy Tommy (Fakultas Teknik Universitas Cenderawasih, 2024)
Landslides are natural disasters that can result in loss of life and property. Therefore, it is necessary to carry out inventory research on areas prone to landslides. The model applied to determine the point of distribution of landslide disasters and areas of potential distribution of landslide disasters is a qualitative descriptive spatial method. Several factors that cause landslides are geology, rock properties, stratigraphy, geological structure, level of weathering and seismicity, climate, rainfall, thick soil, solum. , slope topography, vegetation density and human land use. The results of the analysis show that in Jayaura Regency, Sentani District, there are 3 classes of landslide hazard levels, namely not vulnerable, somewhat vulnerable, quite vulnerable, and vulnerable. In general, Jayapura Regency, Sentani sub-district, is quite prone to the spread of landslides, but there are three sub-districts that are vulnerable, namely Hinekombe sub-district, Sentani village, Bart, Sentani sub-district, Sereh village in the middle and Sentani sub-district, Tollan village,